Correlation network between intestinal bacterial species and differential serum metabolites. - Ji-Xin Zhao (22056386) (2025)
Species–metabolite associations are shown at the species level. Solid lines indicate positive correlations, and dashed lines indicate negative correlations. Edge thickness reflects the correlation strength (Spearman’s correlation coefficient), while node size denotes connectivity (number of associations). Results are shown for (A) the small intestine. (B) the large intestine.